Complications and cares related to the use of the gastrostomy tube in pediatrics (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
To describe the complications and cares related to the use of the gastrostomy tube. Method: A descriptive and exploratory study, with a qualitative approach, performed with 15 mothers of gastrotomized children attended at the Specialized Service in Wounds, Stomas and Incontinence. To obtain the data, it was used an interview with semi-structured script composed by the participants identification and two guiding questions. For the analysis, the thematic type content analysis technique was used. Results: The most frequent complications were accidental tube outlet, hyperemia, granuloma, gastric residue leakage, balloon rupture and ostium enlargement and closure. Conclusion: Gastrostomy care is indispensable for patients, since its guarantee the safety of the procedure, without the risk of complications. The nurse has a responsibility and a privileged position on these patients, since to work with the gastrotomized child is to build a close and collaborative relationship with the child and the family and to contribute to the scientific enhancement and the improvement in the quality of nursing care, thus favoring a partnership between the team of professionals and the family.